2016
DOI: 10.4172/2165-7920.1000868
|View full text |Cite
|
Sign up to set email alerts
|

Ca Prostate with Oral Metastases: A Case Report and Literature Review

Abstract: The oral cavity is a very rare site for metastases, it was described in a number of cancers e.g. lung, breast, colon and prostate cancers. Prostate cancer with oral metastasis is uncommon and accounts for less than 2% of oral malignancies. We report a case of buccal mucosa metastases from ca prostate primary, confirmed by histopathology and immunohistochemistry tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In the present case, the patient reported swelling, pain, and paraesthesia (numb chin syndrome) in the right chin region, thus suggesting the involvement of the mandible. However, the swelling was also present in the right buccal mucosa, indicating that the lesion had involved not only the mandible but also the oral soft tissue, similar to a case reported by Mohamed and Suleiman [8]. The other clinical features that have been reported in oral metastasis of prostate cancer are trismus or limited mouth opening [7] and necrotic bone due to medication-induced osteonecrosis [12].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the present case, the patient reported swelling, pain, and paraesthesia (numb chin syndrome) in the right chin region, thus suggesting the involvement of the mandible. However, the swelling was also present in the right buccal mucosa, indicating that the lesion had involved not only the mandible but also the oral soft tissue, similar to a case reported by Mohamed and Suleiman [8]. The other clinical features that have been reported in oral metastasis of prostate cancer are trismus or limited mouth opening [7] and necrotic bone due to medication-induced osteonecrosis [12].…”
Section: Discussionsupporting
confidence: 77%
“…In this case, the patient was a known case of end-stage prostate cancer, as in cases reported previously in the literature [6][7][8]. The time interval between the diagnosis of prostate cancer and the occurrence of metastasis to the mandible ranges from 2 months [8] to 120 months [6].…”
Section: Discussionmentioning
confidence: 75%
“…In their reported case, the patient had reported having swelling, pain, and paraesthesia (numb chin syndrome) within his right chin region, which had indicated the involvement of the mandible. Nevertheless, the swelling was also not found present within his right buccal mucosa, which had suggested that the lesion had involved not only the mandible but also the oral soft tissue, which was similar to a case that had been reported by Mohamed and Suleiman [24].…”
supporting
confidence: 83%
“…The time interval between the diagnosis of prostate cancer and the occurrence of metastasis to the mandible has ranged from 2 months [24] to 120 months [22]. It was 45 months in their reported case.…”
Section: ] [23] [24] •mentioning
confidence: 83%